SIRI' IN THE PERSPECTIVE OF ISLAMIC VALUES AND CURRENT ISSUE - Deni Iriyadi (Laboratorium Bantenologi UIN Sultan Maulana Hasanuddin Banten, 2022)
This study aims to see how the siri' culture is the philosophy of life for the Bugis people in living their lives. In addition, in this study, the siri' attitude will be reviewed from the point of view of contemporary Islamic values. This research is a qualitative research with a literature study approach. Various references related to siri' culture and Islamic values ​​about that culture to how the implementation of siri' culture is currently used as material for this research study. The results showed that there was a correlation between the Bugis people's philosophy of life in the siri' culture and Islamic values. The relationship lies in a condition where a person must always place themselves according to their nature. Always instill in yourself the nature of siri 'so that the pattern of life can run as well as possible. In Islam, cities are commanded to always obey Allah's commands and stay away from His prohibitions. If someone has siri' nature, then that person will always behave in accordance with the corridors of applicable laws and norms. However, currently the siri' culture has experienced a shift in meaning. Various behaviors that were once very hard to do, are now considered normal and even become something to be proud of. Therefore, we should return the dignity of the siri culture as it should be.